2020
DOI: 10.1111/rda.13637
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of leptin in pregnant and non‐pregnant bitches

Abstract: Leptin regulates body weight and several physiological processes including reproduction. We evaluated the circulating levels of leptin in pregnant and non‐pregnant bitches as well as their correlation with body weight, food intake and number of foetuses. Nineteen healthy German shepherd bitches were used and divided in two groups (pregnant n = 12 and non‐pregnant n = 7). Blood samples were collected every 15 days starting from ovulation (Day 0) throughout pregnancy (pregnant group, P) or throughout luteal phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…By using weekly sampling, these authors highlighted short-term changes during pregnancy, especially in insulin and leptin. These changes suggested a condition of insulin and leptin resistance that characterizes the pregnancy of many mammals including women [30,32,[42][43][44][45]. In the present study, the changes were assessed at longer intervals but the concentrations at early and late pregnancy were comparable to those of Menchetti et al [31].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…By using weekly sampling, these authors highlighted short-term changes during pregnancy, especially in insulin and leptin. These changes suggested a condition of insulin and leptin resistance that characterizes the pregnancy of many mammals including women [30,32,[42][43][44][45]. In the present study, the changes were assessed at longer intervals but the concentrations at early and late pregnancy were comparable to those of Menchetti et al [31].…”
Section: Discussionsupporting
confidence: 54%
“…In fact, during this physiological status, the pregnant animal enhances the feed intake and the mobilization of the body reserves as an adaption mechanisms to the modification in energetic request [26][27][28]. Different hormones (insulin, leptin, T3, T4 and cortisol) and metabolites such as glucose and non-esterified fatty acids (NEFA) are implicated in maintaining energy homeostasis during pregnancy in different species [29][30][31][32]. To our knowledge, no studies have evaluated the impact of the goji berries enriched diet on the hormonal control of the energetic homeostasis during pregnancy of the rabbit does.…”
Section: Introductionmentioning
confidence: 99%
“…Leptin could also have functions in the metabolic allocation of nutrients during the transition from pregnancy to lactation, when the energetic priority shifts from the building of energetic stores within the body to the release of energy from these stores (Block et al, 2001). Results of the present study indicated leptin concentrations return to concentrations similar to those of PP does during late pregnancy and after birth which also occurs in women, bitches, and cows but not in ewes (Block et al, 2001;McFadin et al, 2002;Pérez-Pérez et al, 2018;Troisi et al, 2020).…”
Section: Discussionmentioning
confidence: 49%
“…Plasma leptin concentrations are greater in P compared with PP does, particularly in the second and third week of pregnancy (about +20%). There is also this leptin pattern in women, rodents, cows, and bitches (Kawai et al, 1997;Block et al, 2001;Reitman et al, 2001;Cardinali et al, 2017;Troisi et al, 2020); however, both the biological and physiological functions of leptin appear to be species-specific during pregnancy. The increase observed in the P does appears to be lesser than in other species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation